Signifikansi Ilmu-ilmu Al-Quran untuk Pengembangan Ilmu Dakwah - Moh. Ali Aziz (Islamica: Jurnal Studi Keislaman, 2009)
This paper first of all believes that the concept and theories of the science of the Quran may be appropriated to develop the science and method of dakwah. The old method of dakwah ?as it were- is concerned primarily with how the teachings of Islam and its tenets are to be propagated. The new method in the meantime one that we prefer- should rather focus on how these teachings may be understood by the objects of the dakwah. Hence understanding is the key. The paper further holds that these two methods old and new- are in fact interrelated and that their foundational legitimacies are to be found in the Quran. This paper will slightly touch on this. But a great portion of it will pay attention to the idea of the appropriation of the science of the Quran by the science of dakwah, one that we believe may open up a new horizon in dakwah activities and lead to a moderate, realistic and idealistic as opposed to liberalistic and fundamentalistform of dakwah.